2012
DOI: 10.1002/cncr.27640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body mass index on the outcome of children with acute myeloid leukemia

Abstract: BACKGROUND The effect of body mass index (BMI) on treatment outcome of children with acute myeloid leukemia (AML) is unclear and needs further evaluation. METHODS Children with AML (n=314) enrolled in 4 consecutive St. Jude protocols were grouped according to BMI (underweight, <5th percentile; healthy weight, 5th to 85th percentile; and overweight/obese, ≥ 85th percentile). RESULTS Twenty-five (8.0%) patients were underweight, 86 (27.4%) overweight/obese, and 203 (64.6%) had healthy weight. Five-year overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 28 publications
(50 reference statements)
5
67
7
1
Order By: Relevance
“…This speculation is in part contrasted by Hijiya et al 39 who have shown that in pediatric ALL, there is no statistical difference in pharmacokinetics of cytarabine between normal and overweight patients. Previous studies have found increased TRM in overweight 12 and obese 13 patients with AML resulting in poorer outcome for this group; in this cohort, however, none of 9 TRM cases in children over one year of age were overweight. In contrast, we surprisingly found a trend for being overweight at diagnosis being associated with superior outcome in children aged 10-17 years [unrelated to t(8;21) status], similar to what has been reported in adults with AML.…”
Section: A B C Dcontrasting
confidence: 50%
See 3 more Smart Citations
“…This speculation is in part contrasted by Hijiya et al 39 who have shown that in pediatric ALL, there is no statistical difference in pharmacokinetics of cytarabine between normal and overweight patients. Previous studies have found increased TRM in overweight 12 and obese 13 patients with AML resulting in poorer outcome for this group; in this cohort, however, none of 9 TRM cases in children over one year of age were overweight. In contrast, we surprisingly found a trend for being overweight at diagnosis being associated with superior outcome in children aged 10-17 years [unrelated to t(8;21) status], similar to what has been reported in adults with AML.…”
Section: A B C Dcontrasting
confidence: 50%
“…To our knowledge, no previous studies have reported such a thorough review of toxicities and associations with age and body weight at diagnosis, though many studies suggest similar associations. 12,13,18,19,26,27 We found a trend for age 10-17 years being associated with poorer survival. In contrast to previous studies, 12,13 we found a trend for being overweight being associated with improved survival in children aged 10-17 years.…”
Section: © Ferrata Storti Foundationmentioning
confidence: 60%
See 2 more Smart Citations
“…This has also been shown in pediatric acute myeloid leukemia. 42,43 This U-shaped association seems logical as both weight status and weight change affect and/or can be affected by disease severity. Overweight patients may have a compromised outcome as a result of a deficient immune response due to higher levels of sex steroids, insulin, insulin-like growth factor and inflammatory parameters and have an increased risk of comorbidities related to their excess weight.…”
Section: Discussionmentioning
confidence: 99%